The Practice of Prophetic Imagination : Preaching an Emancipating Word - Brueggemann, Walter (Book collections on Project MUSE., 2012)
The necessary context of prophetic preaching, Walter Brueggemann argues, is "a contestation between narratives": the dominant narrative of our time, which promoting self-sufficiency at the national level (through militarism) and the personal (through consumerism), and the countervailing narrative of a world claimed by a God who is gracious, uncompromising-and real. In previous work Brueggemann has pointed us again and again to the indispensability of imagination. Here he writes for those who bear responsibility for regular proclamation in communities of faith, describing the discipline of a pr